(untitled) (Archives of Criminology, 2023)
The article is based on research carried out as part of the international research project ‘Demand for Sexual Exploitation in Europe (DESIRE)’, covering Croatia, the Netherlands, Poland, and Sweden. The project, financed by the European Commission, was implemented in 2017–2018. The purpose of this publication is to discuss one of the aspects of this research, namely, the functioning of various forms of sexual services other than prostitution. In this context we focussed our study on such phenomena as erotic massage, phone sex, peep shows, or ‘sponsorship’. The starting point of our considerations is the question of whether some forms of satisfying someone’s sexual needs can lead to the exploitation of those who do it. That is why we first present a detailed description of all these phenomena, while in the description we take into account the similarities and differences between the discussed forms and typical prostitution. As one of the goals of the DESIRE project was to establish the relationship between legal regulations and the scale of the sex industry, we analyse the legal and sociopolitical aspects of providing sexual services other than prostitution in the four countries mentioned above. The selection of these four countries is not accidental, because they represent four models of regulating the provision of sexual services that currently function in Europe: from full penalisation (Croatia) to full legalisation (the Netherlands). On the other hand, we looked at these alternative forms of commercial sex from the perspective of human trafficking. Answering the key question of this article, we attempted to indicate the situations and elements of sexual services other than prostitution in which the persons providing them may be exposed to sexual abuse or trafficking.